Children of the streets of Richmond, 1865-1920 - Ward, Harry M. (McFarland & Company, Inc., Publishers, 2015)
"Richmond in the late 19th century was not the genteel peaceful community historians have made it. Virginia's capital was cosmopolitan, boisterous and crime-ridden. The juvenile delinquents of Richmond were held accountable in the Police Court. What emerges from the public record is a picture of what life was really like in the post-Reconstruction urban South"--